USE OF TECHNOLOGY IN TEACHING HUMAN ANATOMY: An Overview (Interdisciplinary Studies Journal, 2025)
Introduction: Transformations in the healthcare field, characterized by the introduction of new disciplines and the transition to competency-based teaching methods, have had a substantial impact on the teaching of anatomy. As a result, there has been a shift in the role played by cadaver dissection, which has incorporated contemporary technologies such as plastic models and multimedia packages. In this context, the inclusion of technology in educational programs requires a careful, evidence-based approach. This study aims to investigate the use of technologies in teaching human anatomy to health science students, with an emphasis on the technological tools used and the results obtained. Methodology: A literature overview was conducted with studies published in the last 10 years. Studies in the form of articles with free access were included. The DeCSMeSH descriptors used and their combinations were applied to the Medline (via Pubmed), Lilacs, and Scielo databases. The selection of articles was made on the Rayyan platform, according to established inclusion and exclusion criteria, in a blinded process by two reviewers. At the end of the process, 8 articles were included. Results: The results obtained were described in text and organized in a table. The data observed showed the growing use of technologies in teaching human anatomy, focusing on the use of computers, tablets, 3D resources, and augmented reality. Conclusion: The current teaching landscape in the health field reveals a tendency towards adopting innovative educational technologies. Methodologies that incorporate technology into traditional anatomy laboratory environments have proven effective, promoting student satisfaction, self-confidence, and engagement.
Keywords: Anatomy; Medical Education; Health Education; Educational Technology; Technological Development